Strategi Membangkitkan Motivasi Belajar Anak Dimasa Pandemi Covid-19 - Muhammad Fahmi; Resti Novianti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
systems. Online learning has its various limitations, such as the lack of gartificial facilities (phones, laptops, and tablets), a lack of understanding of digital media, limited ability to purchase pulse, and signal limitations. Online learning is not only a technical problem, but essence or the purpose of learning has not really tested its effectiveness in online learning systems. he student who is accustomed to face-to-face study and is directly explained with the teacher, now that the teacher gives only the reading instruction and assignments-is making the student even more confused by the lack of a clear explanation but is forced to understand by working on a task. The number of subjects a student takes is the same as the number of tasks the student will complete. With so many assignments the students are psychologically depressed. The study USES descriptive qualitative research that describes the study guide service in reducing the student's learning difficulty at the covid-19 period. The solution is given to the student and then seen the guidance services learn in reducing the student's learning difficulties then several students are taken to interview the teacher's strategy in learning. During the course of instruction, the student always asks for help with chores or simply explaining material that he or she does not understand. With this being the answer that students need a chaperone in study, until the material can be absorbed optimally. Parents should be extra in watching students study while learning online.